The Effectiveness of Film Music in Creating Comedic and Dramatic Atmospheres in the Short Fiction Film "Jarene" - trilaksono, yunanto; Karsam, Karsam; Tuahuns, Rizky Machmud Adi Pratama (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
This research aims to analyze the effectiveness of musical accompaniment in creating a comedic and dramatic atmosphere in the fictional short film titled "Jarene". Music, as an audio element in film, plays a crucial role in enhancing visual narratives and the audience's emotions. The method used in this study is descriptive qualitative with a semiotic and audiovisual aesthetic analysis approach. Data were obtained through direct observation of the film "Jarene", interviews with the filmmakers, and literature studies related to film music theory and dramaturgy. The results indicate that the selection of music type, tempo, harmony, and synchronization with visual scenes can effectively create a contrast in atmosphere between comedic and dramatic segments in the film. Fast paced music with light melodies tends to enhance the comedic tone, while slow tempo music with minor harmonies is effective in depicting dramatic moods. This study concludes that well designed musical accompaniment can enhance the quality of emotional delivery and strengthen the narrative message in short films. These findings are expected to serve as a reference for filmmakers in utilizing music elements to support the atmosphere in their audiovisual works.